Islam in an era of nation-states politics and religious renewal in Muslim Southeast Asia - Hefner, Robert W. 1952-; Horvatich, Patricia 1962- (University of Hawai'i Press, 1997)
"The opening chapters of the volume document relations between the state and prominent Islamic political organizations. A second group of essays brings the level of documentation and analysis one step closer to the grass-roots operation of "reformist" or "resurgent" Islamic movements. The final group shifts the description and analysis to the most basic level - the grass-roots reception of institutional discourse and the target of reformist and resurgent activity. Collectively the essays provide crucial insights into the diversity and complexity of the reception and actualization of Islamic reform. They build a convincing argument for viewing resurgent Islam in Southeast Asia as neither monolithic nor antithetical to the nation-state. The portrait of these movements presented here is sympathetic but critical and does much to advance our understanding of the region and of the role of Islam in shaping its past and future."--BOOK JACKET. "Islam in an Era of Nation-States will be of interest to students of Islam, Southeast Asian history, and the anthropology of religion. In examining the politics and meanings of Islamic resurgence, it will also speak to political scientists, religious scholars, and others concerned with culture and politics in the late modern era."--BOOK JACKET